Hans Jonas and the Ethics of Human Subjects Research - Diekema, Douglas S. (The Hastings Center report, 2020)
In the 1960s, human experimentation and public funding of research increased significantly, and with the rise of the modern teaching hospital, the distinction between clinical care and experimentation became more and more blurred. Yet little in the way of meaningful government regulation existed in the United States prior to 1970. In 1966, Paul Freund, the president of the American Academy of Arts and Sciences, appointed an interdisciplinary working group to consult on the issues being raised by human experimentation. Contributions from the group were published in a 1969 issue of Daedalus titled Ethical Aspects of Experimentation with Human Subjects. In the lead essay, Hans Jonas challenged then-conventional understandings of the moral problems posed by research involving humans and argued for an alternative moral framework. To Jonas, it mattered whether the physician was trying to make the patient well rather than trying to find out how to improve the health of future patients.